A Comparison Between Direct Telehealth and In-Person Methods of Teaching Expressive Labels to Children Diagnosed With Autism Spectrum Disorder. Issue 2 (March 2023) - Knopp, Kandice; Ferguson, Julia L.; Piazza, Jessica; Weiss, Mary Jane; Lee, Matthew; Cihon, Joseph H.; Leaf, Justin B.
Recent behavior analytic research has demonstrated that the provision of applied behavior analytic services via direct telehealth can be an effective teaching modality for some learners with autism spectrum disorder (ASD). Historically, teaching procedures based on applied behavior analysis (ABA), including discrete trial teaching (DTT), have been provided and evaluated via in-person delivery. This study sought to compare the implementation of DTT via direct telehealth to DTT implemented in-person within and across participants. Specifically, this study evaluated the two delivery modalities in terms of skill acquisition, maintenance, efficiency, and learner responding during teaching sessions. Results of an adapted alternating treatments design nested into a multiple baseline design demonstrated that all three participants diagnosed with ASD met the mastery criteria for the expressive labels taught. Areas of future research, participant prerequisite skills, and clinical implications will be discussed in the context of these results.